PENERAPAN ALGORITMA KRUSKAL DAN ALGORITMA SOLLIN PADA PENDISTRIBUSIAN AIR PDAM TIRTA AJI CABANG WONOSOBO DAN APLIKASINYA MENGGUNAKAN MICROSOFT VISUAL BASIC 6.0 - Prasetiyo, Agustaf; Mulyono, Mulyono; Mashuri, Mashuri (Unnes Journal of Mathematics, 2018)
Kruskal algorithm and Sollin algorithm are algorithms on graph theory which can be used to find minimum spanning tree for weighted graph. The problem in this research is how the result of minimum water distribution of Tirta Aji Municipal Waterworks Wonosobo branch that in the form of minimum spanning tree using Kruskal algorithm and Sollin algorithm, and how to build an application to find minimum spanning tree from water pipes distribution of Tirta Aji Municipal Waterworks Wonosobo branch using Microsoft Visual Basic 6.0 from Kruskal algorithm and Sollin algorithm. Based on the obtained secondary data, it can be arranged a network. From this network it can be obtained the minimum spanning tree by using Kruskal algorithm and Sollin algorithm. Kruskal algorithm and Sollin algorithm were applied to build an application on Microsoft Visual Basic 6.0, then that application can be used to find the minimum spanning tree from the water pipes distribution. Based on the result of this research, it can be concluded that the weight of minimum spanning tree using Kruskal algorithm, Sollin algorithm and this application is same, that is 36.715 m. It means, the water pipes distribution of Tirta Aji Municipal Waterworks Wonosobo branch can be thrifted up to 9.027 m from the total pipes length before, that is 45.742 m. Kruskal and Sollin algorithm are algorithms on graph theory which can be used to find minimum spanning tree. The problem in this research is how the result of minimum water distribution of Tirta Aji Municipal Waterworks using Kruskal algorithm and Sollin algorithm, and how to build an application to find minimum spanning tree from water pipes distribution of Tirta Aji Municipal Waterworks using Microsoft VB 6.0 from Kruskal and Sollin algorithm. Based on the obtained secondary data, it can be arranged a network. From this network it can be obtained the minimum spanning tree by using Kruskal and Sollin algorithm. Kruskal and Sollin algorithm were applied to build an application on Microsoft VB 6.0, then that application can be used to find the minimum spanning tree from the water pipes distribution. Based on the result of this research, it can be concluded that the weight of minimum spanning tree using Kruskal algorithm, Sollin algorithm and this application is same, that is 36.715 m. It means, the water pipes distribution of Tirta Aji Municipal Waterworks can be thrifted up to 9.027 m from the total pipes length before, that is 45.742 m